Papillary variant of hemangiopericytoma – a rare morphological variant presenting as a recurrent occipital tumor - Salapathi S; Rajeshwari B; Mitra Ghosh (Tropical Journal of Pathology and Microbiology, 2019)
Solitary fibrous tumor / Hemangiopericytoma (SFT/ HPC) of central nervous system are the most common mesenchymal nonmeningothelial neoplasms, accounting for <1% of all primary central nervous system (CNS) tumors and most commonly affects adults. Histologically two morphological types exist, the SFT phenotype and the HPC phenotype. Tumors with the hemangiopericytoma phenotype have a high rate of recurrence and may develop extracranial metastases. Papillary morphology is unusual in SFT/ HPC and only four cases of HPCs with a papillary pattern have been reported in the literature. Ours is probably the fifth reported case. Papillary variant of HPC is a rare morphological variant, and its differential diagnosis includes other primary intracranial tumors with papillary pattern like papillary meningioma, papillary ependymoma or metastatic carcinoma, which the pathologists and clinicians should bear in mind before making the correct diagnosis. Even after gross total resection, HPC have high rate of recurrence, and patients benefit from adjuvant radiotherapy.